Bridget Jones's diary - Maguire, Sharon; Bevan, Tim.; Fellner, Eric.; Cavendish, Jonathan; Fielding, Helen, 1958-; Davies, Andrew, 1936-; Curtis, Richard, 1956-; Zellweger, Renee, 1969-; Firth, Colin, 1960-; Grant, Hugh.; Broadbent, Jim.; Jones, Gemma; et al. (Burbank, CA : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2001)
In her mid-thirties, still single and still being set up with dates by her mom, Bridget decides she needs to make a change in her life. She falls for her boss who uses her and then dumps her. In the meantime, Bridget keeps running into the divorced guy her mom tried to set her up with, and he happens to be ex-friends with her boss. She uses her diary as a confessional and she begins to wonder if she will ever find true love.
Opening credits/"My thirty-second year of being single" -- Keeping resolutions -- "Is skirt off sick?" -- "Oratorical fireworks" -- "Bridget Jones, Wanton Sex Goddess" -- "A Full-Blown, Mini-Break, Holiday Weekend" -- Tarts and vicars? -- "Is there someone here?" -- "I'm Every Woman" -- Bonfires and smug married couples -- Darcy's exclusive interview -- "To Bridget, Just as She Is" -- "Should I bring my dueling pistols, or my sword?" -- "I just don't work without you" -- "You're a nice man and ... I like you" -- "Diaries are just full of crap" -- End credits.
Based on the novel by Helen Fielding.
Special features: audio commentary by director Sharon Maguire; making-of featurette; two music videos: Shelby Lynn's "Killin' Kind" and Gabrielle's "Out of Reach"; deleted scenes; international end credit sequence; original Bridget Jones columns.
Director of photography, Stuart Dryburgh ; editor, Martin Walsh ; original music, Patrick Doyle ; costume designer, Rachael Fleming ; production designer, Gemma Jackson.
Renee Zellweger, Colin Firth, Hugh Grant, Jim Broadbent, Gemma Jones.
MPAA rating: R; for language and some strong sexuality.
DVD, region 1, NTSC, dual-layer format, widescreen (2.35:1); Dolby digital 5.1 surround.
Keywords: Fielding, Helen, -- 1958- -- Film adaptations; Jones, Bridget -- (Fictitious character) -- Drama; Man-woman relationships -- Drama; Women -- Diaries -- Drama; Single women -- England -- London -- Drama; Comedy; Women; England -- London; DVD-Video discs; Feature films -- Great Britain; Feature films -- France; Comedy films; Drama; Feature films; Films for the hearing impaired; Film adaptations; Romance films; Video recordings for the hearing impaired